2007
DOI: 10.1111/j.1743-6109.2007.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensation and Sexual Arousal in Circumcised and Uncircumcised Men

Abstract: Introduction Research, theory, and popular belief all suggest that penile sensation is greater in the uncircumcised as compared with the circumcised man. However, research involving direct measurement of penile sensation has been undertaken only in sexually functional and dysfunctional groups, and as a correlate of sexual behavior. There are no reports of penile sensation in sexually aroused subjects, and it is not known how arousal affects sensation. In principle, this should be more closely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 19 publications
1
62
1
1
Order By: Relevance
“…1 Circumcision is generally considered as a simple, rapid operation with efficacy for protection against HIV and other sexually transmitted infections, as confirmed in numerous, highquality studies. [2][3][4][5][6][7] Circumcision has been reported to adversely affect sexual function; 8 however, the majority of studies, including highquality ones [9][10][11] and ones with data arising from randomized controlled trials (RCTs), 12,13 show no difference or improvement in sexual function, sensitivity and satisfaction after circumcision. All of the data were considered by the American Academy of Pediatrics in formulating its 2012 policy, which concluded that there were no adverse effects on these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…1 Circumcision is generally considered as a simple, rapid operation with efficacy for protection against HIV and other sexually transmitted infections, as confirmed in numerous, highquality studies. [2][3][4][5][6][7] Circumcision has been reported to adversely affect sexual function; 8 however, the majority of studies, including highquality ones [9][10][11] and ones with data arising from randomized controlled trials (RCTs), 12,13 show no difference or improvement in sexual function, sensitivity and satisfaction after circumcision. All of the data were considered by the American Academy of Pediatrics in formulating its 2012 policy, which concluded that there were no adverse effects on these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…(10,115,116) The more important issue of penile sensation during sexual arousal was addressed in a recent thermal imaging study which found no difference. (117) In fact sensitivity decreased similarly in both groups during arousal! Baseline penile temperature was lower in the uncircumcised men, in whom the monitor was under the prepuce, just below the glans.…”
Section: Cervical Cancermentioning
confidence: 99%
“…131,[134][135][136] There is fair evidence that no significant difference exists between circumcised and uncircumcised men in terms of sexual function, as assessed by using the IELT. 129 Limitations to consider with respect to this issue include the timing of IELT studies after circumcision, because studies of sexual function at 12 weeks postcircumcision by using IELT measures may not accurately reflect sexual function at a later period.…”
Section: Sexual Functionmentioning
confidence: 99%